Conflict Management in Organisations: Case of Albania - Agaj, Desara (European Journal of Multidisciplinary Studies, 2023)
Nowadays, people spent almost one-third or even more of their life at work. During these hours relations with colleagues play an important role in the overall well-being of the employees, leading to job satisfaction and high performance. Sometimes, the workload, the pressure to finish the work on time, to respect deadlines, and even the daily relations with coworkers, etc., can lead to some conflicts between employees. The way employees manage conflicts happening in organizations has a crucial impact on their well-being and the culture of the organization, making conflict management an important element for human adaptability. The aim of this article is to study conflict management styles that employees in different banks in Albania use in their everyday work. Data analyses are based on the interpretation of forty-six semi-structured interviews with employees in five banks in the city of Tirana. So, qualitative design analyses are used. This study shows us that the dominant style to manage conflicts at work according to the sample that participated in this study is the compromising style.